The Nexus Between Tourism and Environmental Quality in Countries Most Dependent on Tourism: A RALS Approach to the Cointegration Test - Yilmaz, Yenilmez Ufuk; Rezapouraghdam, Hamed; Kilic, Hasan (Mdpi, 2025)
Sustainable tourism encompasses the evaluation of its present and prospective economic, social, and ecological consequences by prioritizing the demands of its natural environment and the local populations. This study examined how tourism affects critical socio-economic variables, such as life expectancy, energy intensity (EI), economic growth (EG), and population, on the environmental quality (EQ) of tourism-dependent countries. The authors employed the newly developed residual augmented least squares (RALS) cointegration econometric method to estimate the long-term associations between the study factors. On the other hand, the autoregressive distributed lag (ARDL) model was used to estimate long- and short-run estimates. The consequences revealed that, in the long run, the population, the EI, and tourism exert positive pressure on carbon emissions. However, in the short run, the EI, EG, life expectancy (LE), and population exert positive pressure to boost emissions, resulting in environmental degradation. Based on these findings, sustainable tourism management and green EG should be given priority to preserve environmental quality.
Keywords: sustainable tourism; economic growth; RALS cointegration; ARDL model; tourism-dependent countries